2015
DOI: 10.3390/w7051808
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Flood Variations in Shanghai over 1949–2009 with Mann-Kendall Tests and a Newspaper-Based Database

Abstract: Abstract:A valuable aid to assessing and managing flood risk lies in a reliable database of historical floods. In this study, a newspaper-based flood database for Shanghai (NFDS) for the period 1949-2009 was developed through a systematic scanning of newspapers. After calibration and validation of the database, Mann-Kendall tests and correlation analysis were applied to detect possible changes in flood frequencies. The analysis was carried out for three different flood types: overbank flood, agricultural water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 46 publications
0
30
0
1
Order By: Relevance
“…For example, a survey of 351 cities across mainland China found that 62 % experienced at least one pluvial flood per year, and that 74.6 % of the cities had been inundated to a depth of more than 50 mm during (Xie 2013. In Shanghai in particular, urban pluvial floods were found to have increased significantly between 1949 and 2009 (Du et al 2015a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a survey of 351 cities across mainland China found that 62 % experienced at least one pluvial flood per year, and that 74.6 % of the cities had been inundated to a depth of more than 50 mm during (Xie 2013. In Shanghai in particular, urban pluvial floods were found to have increased significantly between 1949 and 2009 (Du et al 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…Although disaster databases have been established on global (Guha-Sapir et al 2015), national (Shi et al 2000;Rashid 2011), and regional scales (Llasat et al 2009), only a few databases have detailed urban pluvial floods with high spatial resolution (GRIP 2015). Fine-scale databases have been recently established on the basis of telephone questionnaires (Merz et al 2013), citizen complaints (Gaitan and ten Veldhuis 2015), insurance claims (Spekkers et al 2013), and newspaper reports (Du et al 2015a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mann-Kendall test (M-K test) assessed the trends and abrupt changes in a time series [59], and linear trend analyses were used for temperature analyses [60]; and Ens indicates how well the plot of observed versus simulated data fits the 1:1 line. A value of 0.75 < Ens ≤ 1.00 is very good, 0.65 < Ens ≤ 0.75 is good, 0.5 < Ens ≤ 0.65 is satisfactory, and Ens ≤ 0.5 is unsatisfactory [56].…”
Section: Design Of the Climate Scenariosmentioning
confidence: 99%
“…The Mann-Kendall test (M-K test) assessed the trends and abrupt changes in a time series [59], and linear trend analyses were used for temperature analyses [60]; and the five-year moving average and accumulating anomalies were applied to the precipitation analysis.…”
Section: Design Of the Climate Scenariosmentioning
confidence: 99%